Effect of tillage system and spacing on growth and yield of sugar beet (Beta vulgaris L.), Kassala State, Sudan - A. Mustafa, Moawia; A. EL- Awad, Sheikh El Din; M.H. Basheir, Elwaleed; M.A. Mustafa, Abbas (Gezira Journal of Agricultural Science, 2021)
Field experiments were conducted during 2011- 2013 in Kassala Agricultural Research Station to study the effect of different tillage operations, inter and intra-row spacing, on growth and yield of sugar beet. The experimental design was a split-split-plot design, with three replicates. The treatments used were tillage system (ploughing and harrowing) as the main plot , row spacing (60, 80 and 100 cm) as the sub-plot and intra-row spacing  (10, 20 and 30 cm) as the sub-sub-plot. Statistical analysis revealed  no significant difference between tillage operations on soil clod size distribution. The treatments disc harrow, inter-row spacing of 60cm, intra-row of 20 cm had highly significant (P≤0.001) effect on yield in both seasons. Based on the results of this study, it is recommended to use disc harrow for land preparation and plant sugar beet at an inter and intra- row spacing of 60 and 20 cm.